The biopsychosocial model is lost in translation: from misrepresentation to an enactive modernization - Cormack, Ben; Stilwell, Peter; Coninx, Sabrina; Gibson, Jo (Physiotherapy theory and practice, 2023)
There are increasing recommendations to use the biopsychosocial model (BPSM) as a guide for musculoskeletal research and practice. However, there is a wide range of interpretations and applications of the model, many of which deviate from George Engel's original BPSM. These deviations have led to confusion and suboptimal patient care. 1) To review Engel's original work; 2) outline prominent BPSM interpretations and misapplications in research and practice; and 3) present an "enactive" modernization of the BPSM. Critical narrative review in the context of musculoskeletal pain. The BPSM has been biomedicalized, fragmented, and used in reductionist ways. Two useful versions of the BPSM have been running mostly in parallel, rarely converging. The first version is a "humanistic" interpretation based on person- and relationship-centredness. The second version is a "causation" interpretation focused on multifactorial contributors to illness and health. Recently, authors have argued that a modern enactive approach to the BPSM can accommodate both interpretations. The BPSM is often conceptualized in narrow ways and only partially implemented in clinical care. We outline how an "enactive-BPS approach" to musculoskeletal care aligns with Engel's vision yet addresses theoretical limitations and may mitigate misapplications.